Oportunidade perdida de diagnóstico oportunista para diabetes mellitus em comunidades quilombolas de Vitória da Conquista - Bahia - Claudio Lima Souza (2014)
Diabetes Mellitus (DM) is a metabolic disease, of insidious onset and which causes high morbidity and mortality. It is among the first causes of entry into dialysis programs and cardiovascular diseases, in addition to being the fifth leading cause of death in the world. Because there are no symptoms in the beginning, the diagnosis among asymptomatic patients has been shown to be cost-effective, especially in individuals older than 45 years old and among afrodescendants, who have higher risk of developing DM and present with worse control and more co-morbidities. Current guidelines recommend screening, thru serum glucose levels, in all individuals older than 45 years old, with high Body Mass Index (BMI) and/or hypertension.. Quilombola Communities have presumed afrodescendant origin; they live predominantly in rural areas and have poor socioeconomic conditions and limited access to health services. The objective of this study was to estimate missed opportunity for opportunistic diagnosis of DM (PDO) in quilombola communities from Vitoria da Conquista, Bahia, and its association with sociodemographic variables and those related to health and health services. A population-based survey was carried out in a representative sample (n=797) of individuals from 25 quilombola communities certified by Palmares Foundation, in 2011. The research consisted of the following steps: awareness and georeferencing, with preparation of maps containing photographic identification and geographical coordinates of households, services and community boundaries; application of a semi-structured questionnaire, modified and adapted from the National Survey of Health through HP Pocket Rx5710TM. laptops. Blood pressure and anthropometric measurements were also performed. For this analysis of PDO, 548 individuals were eligible considering the risk criteria for DM: age over 45 years old, high BMI and hypertension. PDO was defined as never having performed the blood glucose determination exam or having it carried our more than 3 years, in reply to question D22 of the instrument "When was the last time that you had blood tests for measuring blood glucose level, i.e., the blood sugar?" The PDO was evaluated against sociodemographic variables (sex, age, self-reported ethnic background, self-assessment of health status, marital status, income, education, smoking, physical activity and alcohol consumption); clinical (chronic diseases history and measurement of arterial blood pressure) and variables related to service (physician consultation in the past twelve months, blood pressure measured in the last year, registration in UBSF (Health Family Basic Unit), number of ACS (Health Community Agent) visits and index of access to health services. Descriptive, univariate and multivariate statistical analysis were performed by software R version 2.11.1 and EPIINFO versions 3.5.1 and 7.0.9.7; statistical significance level was p<0.05. The prevalence of PDO was estimated in 42.6 %. Logistic regression indicated that the following factors were statistically associated with the outcome: health condition self-assessment as good/very good; not measuring blood pressure in last year, not having physician consultation in last twelve months and poor access to services. The high prevalence of PDO reported in this study indicates deficiencies in the strategies for diabetes diagnosis for higher risk in the studied communities, indicating lack of integration in prevention actions. In order to increase effectiveness of early diagnosis in asymptomatic patients, actions at the system level are needed including: training of family health teams to approach populations that present greater risk; empowerment of ACS to assess risk factors during home visits; and, decentralization of blood collecting service for laboratory tests for improvement in access to care. Continuing and integral care among services are needed for better effectiveness. Thus, it is necessary that managers, service providers and users be involved in the streamline of care, from basic to specialized level. Recognizing the greater vulnerability, extreme poverty and poor access to health services in these communities, the actions for the readjustment of care strategy in DM should be prioritized in order to decrease the PDO. This way, equity would be exerted, seeking the reduction of inequalities providing greater support for those who have greater need.